The big leagues go to Washington : Congress and sports antitrust, 1951-1989 - Surdam, David G. (David George) (University of Illinois Press, 2015)
"Between 1951 and 1976 the U.S. Congress held a series of hearings to investigate antitrust aspects of professional sports leagues. Congress was concerned about their cartel-like behavior, which included territorial protection, controlling ownership of players, restricting new franchises, and preventing the formation of competitive leagues. Surdam chronicles the key issues in the major hearings and discusses the direct and indirect consequences of them, sometimes through legislation and more often through public airing of the worst practices. The hearings brought into view the conflicting interests of owners, players, labor and property laws, and major and minor league teams, whose locations and success mattered to members of Congress. The hearings led to relocation of ailing franchises, as legislators from the West and South pressed the league into bringing teams into their states. Other hearings affected broadcasting rights and black-outs, the role of leagues versus their individual franchises, player drafts, player unions, league mergers, and the dominance of the New York Yankees. Surdam pays special attention to the economic issues that arose in each case. The success and survival of the major league teams depended in large part of their ability to avoid congressional interference, and adapting to it when necessary"--